(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the advanced experience of foreign countries in improving the efficiency of bank assets. Asset management plays a crucial role in ensuring the efficiency of the banking system and achieving financial stability. The article highlights the approaches to introducing innovative asset management mechanisms in developed countries such as the USA, the European Union, Japan, and South Korea. This experience can offer new opportunities for Uzbekistan’s banking system and have practical significance in increasing the profitability of local banks. The study is based on international statistical data and proposes prospects and mechanisms for applying advanced foreign practices to the national banking system.